Расширение ШОС: проблемы и перспективы в контексте вступления Ирана (Вестник КазНУ. Серия Востоковедения, 2022)
This article examines the problems and prospects of the SCO enlargement. The admission of India, Pakistan and Iran to the SCO gives impetus to the development of the organization within the geopolitical perspectives. Although the format of strategic, including military-political, cooperation within the organization is a priority in bilateral relations, the SCO has the potential for institutionalization. At the moment, within the SCO, from the standpoint of geopolitics, the balance of power is shifting, and the parties are actively promoting the priorities of economic cooperation. The SCO still faces a dilemma, whether to go through the process of institutionalization or to maintain the current regime of cooperation based on a regional platform. In the spectrum of the development of military-political relations, an important role is played by the shift in the balance of power in relations between Russia, India, on the one hand, and China and Pakistan, on the other. India's diplomatic activity in the framework of the QUAD cooperation, as well as the strengthening of the Sino-Russian strategic partnership, all lead to a change in the existing status quo. Another important aspect is the side of economic cooperation, when Russia and China express ideas about the conjugation of the EAEU and the Belt and Road Initiative, where a number of SCO experts are considered as a platform for strengthening this strategic dialogue.